The content of cadmium in honey from the Republic of Macedonia - Stankovska, Elena; Stafilov, Trajče; Šajn, Robert (Macedonian Journal of Ecology and Environment, 2007)
The content of cadmium in 123 honey samples collected from different parts of the Republic of Macedonia was determined by electrothermal atomic absorption spectrometry. The microwave digestion system was applied for digestion of the samples. It was found that the content of cadmium varies from below detection limit (1.0 µg kg-1) to 267.9 µg kg-1 with the mean content of 3.63 µg kg-1. The highest content of Cd was found in the honey samples from the central part of Macedonia (region of Veles) in connection to the existence of lead, zinc and cadmium smelter plant in this region. Mean value of Cd in honey samples from the region of Veles is three times higher than the determined mean for Macedonia. Relatively high contents are also found in the eastern part of Macedonia which is a consequence of natural enrichment of Cd with the geological formations associated with Pb-Zn mines Sasa and Toranica.